Impact of Temperature, Rainfall and Clearness Index on Global Solar Radiation at Nepalgunj in Nepal - K.C., Bed Raj (Journal of Advanced Academic Research, 2019)
This paper reports the first experimental results on global solar irradiance measured at the horizontal surface since 2017 using calibrated Pyranometer-2 at Nepalgunj (Lat.28.05°N, Lon.81.62°E) which is about 150m from the sea level. This paper explains the impact of temperature, rainfall and clearness Index on the intensity of global solar irradiation. The annual average measured value of GSR 16.02 MJ/m2/day which is sufficient to promote solar active and passive solar energy technology at Nepalgunj and other similar geographic allocations. The results of this research can be utilized for the conformation of variation of solar radiation with meteorological parameters and can be used for location of similar meteorological and geographical sites where solar data are not available.